Generating point clouds for slicing free-form objects for 3-D printing. Issue 2 (23rd February 2017) - Oropallo, William; Piegl, Les A.; Rosen, Paul; Rajab, Khairan
ABSTRACT: 3-D printing, also known as additive manufacturing, has gained a lot of attention both within and outside CAD research. Even popular media have touted the technology as one of the game changer technologies of the 21st century. Simply stated, most printing devices add material to an unfinished part, layer by layer, until the entire object is completed. In order to make this happen, the object is sliced into thin layers which are produced and glued together. Since NURBS are the standard form of modeling tools, the process entails converting the NURBS into an STL model (piecewise triangular model) which is then sliced into a set of closed polygonal loops. In order to avoid the many problems with the STL-based slicing, in this paper we investigate a point cloud-based approach to direct slicing of NURBS based models. It uses the original NURBS model and converts the model into a point cloud, based on layer thickness and accuracy requirements, for direct slicing. The only major computational requirement is point evaluation which can be done error free and in an inexpensive manner. The generation of the point cloud is the main topic of this paper. GRAPHICAL ABSTRACT: